ANALYSIS OF THE AVAILABILITY OF WATER RESOURCES AND CONSERVATION EFFORTS SUB DAS LESTI DISTRICT OF MALANG - Abdul Somat Bukori; Rachmat Boedisantoso (Institut Teknologi Sepuluh Nopember, 2017)
Lesti sub basins is one of the upstream part of the Brantas river basin located in the district of Malang. Conditions Lesti sub-basins have been damaged thereby potentially experiencing a water deficit. The deficit of water in the dry season in 2017 amounted to 2.141.057 m³ and 2023 amounted to 3.881.593 m³.To overcome these deficits conservation efforts both vegetation and mechanically. Area of land required until 2023 with the planting of agarwood trees covering an area of 18,27 km², covering an area of 15,53 km² and a bamboo plant Poran 51,75 km². Needs rainwater harvesting roofs media as much as 3 sump capacity of 24 m³. Embung needs as much as 3 each reservoir capacity of 800.000 m³. Embung investment costs Rp. 207 205 545 000, - done in 2017 until 2018.Financial aspects of the construction of the water reservoir with an interest rate of 7% per year IRR = 13,19%> 7%; BCR, i (7%) = 1,34> 1 and NPV, i (7%) = Rp. 91.152.353.632,-. The construction of such Eligible.